Implementasi Metode Pembelajaran Berbasis Teknologi Dalam Meningkatkan Prestasi Siswa Di MTsN 2 MALANG (MTsN Turen) Kecamatan Turen Kabupaten Malang - Santoso, Kukuh (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
The development of the digital world is followed by developments in the world of education in Indonesia, it is no longer the time to correct educational regulations that must be digital-based but rather the time to correct whether the digital role in education is right on target or not. Almost all educational institutions in Indonesia are always up to date with the development of education in Indonesia, apart from the institutions that move to update, the ministry of education (government) must also move to update to ensure the educational institutions under its auspices are in accordance with the qualifications. the world of education today. So that the existence of a two-way movement has a goal so that students develop optimally both in quality and quantity. Digitization gave rise to developments in educational activities, one of which was the use of technology such as LCDs, computers, internet, and even smartphones to support teaching and learning activities. At MtsN 2 Malang has maximized the use of technology for learning activities, which makes the school more communicative so as to stimulate student interest in learning and improve achievement. In terms of teaching and learning activities, the focus of this research is on: how to use technology in teaching and learning activities at MtsN 2 Malang, whether positive changes in students are clearly visible with the use of learning technology, and the qualifications of teaching teachers at MtsN 2 Malang. This study uses a qualitative and descriptive research approach in the form of the type of reading being studied. The type of research used is a case study conducted in an incentive, detailed, and in-depth manner towards a particular institution, organization, and group. The procedure for collecting data is through interviews, observation, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions.